Framework Convention for the protection of national minorities : collected texts (Council of Europe Publishing, 2005)
The protection of national minorities is a core issue for the Council of Europe, and one of the major achievements in this field is the Framework Convention for the Protection of National Minorities. The entry into force of the Framework Convention on 1 February 1998 was indeed an event of universal stature, for it is the first ever legally binding multilateral instrument devoted to the protection of national minorities in general. Its importance is widely acknowledged, and the number of ratifications has grown rapidly. Simultaneously, an emphasis is being placed on the implementation and on the efficient functioning of the monitoring mechanism of the Framework Convention. This collection provides all those interested in the protection of national minorities a user-friendly compilation of the basic texts concerning the Framework Convention. In addition to the Framework Convention and its explanatory memorandum, the collection contains texts pertaining to the monitoring mechanism in general and the Advisory Committee in particular. It further provides the state of signatures and ratifications as well as declarations and reservations. It also contains a list of State Reports received and Opinions of the Advisory Committee adopted under both the first and second cycles of monitoring.